A dengue e seu vetor : uma sequência de ensino investigativo em uma perspectiva inovadora - Nélio, Thamiris Silva (2022)
The investigation of pedagogical strategies in face-to-face classes in Basic Education Biology Teaching that is more attractive to students has been widely propagated and disseminated in education but at a time of the global pandemic. This is even more necessary, intensifying the strategies, concomitant with the model of non-face-to-face classes. To Persuade the educational challenges, there is also a high rate of endemic diseases such as Dengue, bringing great harm to the population. The objective of this work was to use new strategies in the Biology Teaching-Learning process, based on the Investigative Teaching sequence associated with Active Learning Methods - MAA on the theme of Dengue and its vector, aiming at the production of pedagogical material to trace paths aiming at scientific literacy in the absence of face-to-face classes. We chose to use qualitative methods with questionnaires and interviews aimed at Biology teachers, pedagogical strategies adopted on the subject in online classes were raised, and the validation of the educational products produced. Data analysis and presentation of resources are based on Bardin's content analysis, as it is a method widely used in this type of research. The materials produced contain the SEI on Dengue and its vector and the Denguelogia 4.0 website, the first have been built within the website and perceived as a Virtual Didactic Guide. The SEI considered an innovative and consistent proposal as a path to scientific literacy by collaborating teachers. In this way, we aim to bring new methodological strategies to Biology classes, providing teachers with a more accessible and adjustable didactic support to a new reality.